Building urban resilience through change of use - aRemøy, Hilde Therese 1972- (Innovation in the built environment, 2018)
"Describes all aspects of sustainable conversion adaptation of existing buildings and provides solutions for making urban settlements resilient to climate change"--Provided by publisher.